chứng minh: \(\sin^6x+cos^6x=1-3\sin^2x.\cos^2x\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(P=\sqrt{x^4+x^2y^2}+x^2=\sqrt{x^4+\frac{1}{x^2}}+x^2\)
Ta có: \(x^4+\frac{1}{x^2}=x^4+\frac{1}{8x^2}+\frac{1}{8x^2}+...+\frac{1}{8x^2}\ge9\sqrt[9]{x^4.\left(\frac{1}{8x^2}\right)^8}\)
\(=9\sqrt[9]{\frac{1}{8^8.x^{12}}}\)
=> \(P=3\sqrt[18]{\frac{1}{8^8.x^{12}}}+x^2\)
\(=\sqrt[18]{\frac{1}{8^8x^{12}}}+\sqrt[18]{\frac{1}{8^8x^{12}}}+\sqrt[18]{\frac{1}{8^8x^{12}}}+x^2\)
\(\ge4\sqrt[4]{\left(\sqrt[18]{\frac{1}{8^8x^{12}}}\right)^3.x^2}\)
\(=4.\left(\frac{1}{8^{\frac{1}{3}}.x^{\frac{1}{2}}}\right).x^2=2\)
Dấu "=" xảy ra <=> \(\hept{\begin{cases}x^4=\frac{1}{8x^2}\\x^2=\sqrt[8]{\frac{1}{8^8x^{12}}}\end{cases}}\)<=> x^2 = 1/2 khi đó y = 2 , x = \(\frac{1}{\sqrt{2}}\)
Vậy GTNN của P = 2.
Ta có: \(\sin^6x+\cos^6x=\left(\sin^2x\right)^3+\left(\cos^2x\right)^3\)
\(=\left(\sin^2x+\cos^2x\right)^3-3\left(\cos^2x+\sin^2x\right)\cos^2x.\sin^2x\)
\(=1-3\sin^2x.\cos^2x\)